Social Science Perspectives on Global Public Health - La Placa, Vincent; Morgan, Julia (Routledge, 2022)
Approaching global health through a social justice lens, this text explores both established and emerging issues for contemporary health and wellbeing. Divided into two parts, the book introduces key concepts in relation to global public health, such as ethics, economics, health disparities, and globalisation. The second part comprises chapters exploring specific challenges, such as designing and implementing public health interventions, the role of social enterprise, climate change, sustainability and health, oral health, violence, palliative care, mental health, loneliness, nutrition, and embracing diverse genders. These chapters build on, and apply, the theoretical frameworks laid out in part one, linking the substantive content to broader contexts. Taking an inclusive, global approach, this is a key text for both undergraduate and postgraduate students of global health, public health, and medical sociology.